Household and Community Assets and Farmers' Adaptation to Extreme Weather Event: the Case of Drought in China - Yang-jie WANG; Ji-kun HUANG; Jin-xia WANG (Journal of Integrative Agriculture, 2014)
Under climate change, rising frequency and serious extreme weather events have challenged agricultural production. Designing appropriate adaptation measures to the extreme weather events require rigorous and empirical analysis. The overall goals of this study are to understand physical adaptation measures taken by farmers and the impacts of household and community assets on farmers' adaptation when they face drought. The analyses are based on a unique data set collected from a household survey in three provinces in China. The survey results show that though not common on annual basis, some farmers did use physical adaptation measures to fight drought. Regression analysis reveals that both household and community assets significantly affect farmers' adaptation behaviors. Improving households' social capital and wealth, communities' network and access to government's anti-drought service can facilitate farmers' adaptation to drought. Results indicate that community's irrigation infrastructure and physical adaptation taken by farmers can substitute each other. Further analysis shows that the households taking adaptation measures have higher crop yields than those without taking these measures. The paper concludes with several policy implications.